Discrimination based on gender in the recruitment and selection process-young adults’ perspective - Krysztofiak, Katarzyna (Olsztyn Economic Journal, 2023)
The article addresses the issue of the scale of gender discrimination in the recruitment and selection process among young adults. The intensity of the examined phenomenon occurring in job advertisements and during the recruitment interview was identified, which, despite its low frequency, may significantly affect the future functioning of the labor market. Additionally, it was examined what impact the phenomenon they experienced had on the respondents, on their self-esteem and way of thinking. The overwhelming percentage of negative impact and unpleasant memories was intertwined with young adults’ indifference to gender discrimination directed at them. The topic covered in the study is broad and requires interest and in-depth study.